On a Piece of Paper an a Pair of Scissors - François Dubeau (Journal of Basic & Applied Sciences, 2015)
We discuss the problem of splitting a given geometrical plane figure in two regions of equal area by drawing a line through a given point in the plane. We also discuss the possibility of splitting the figure into regions in proportions p% and (1 - p)% of the area of the given figure.